2021
DOI: 10.3390/gels7040207
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Application, Patent Repository, Clinical Trial and Regulatory Updates on Hydrogel: An Extensive Review

Abstract: Hydrogels are known for their leading role in biomaterial systems involving pharmaceuticals that fascinate material scientists to work on the wide variety of biomedical applications. The physical and mechanical properties of hydrogels, along with their biodegradability and biocompatibility characteristics, have made them an attractive and flexible tool with various applications such as imaging, diagnosis and treatment. The water-cherishing nature of hydrogels and their capacity to swell—contingent upon a few e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 121 publications
0
22
0
Order By: Relevance
“…156,161 Stimuli-sensitive smart drug delivery carriers can be produced using BC hydrogels. 162 In this context, Park et al…”
Section: Recent Advances On Bacterial Cellulose For the Delivery Of A...mentioning
confidence: 99%
See 1 more Smart Citation
“…156,161 Stimuli-sensitive smart drug delivery carriers can be produced using BC hydrogels. 162 In this context, Park et al…”
Section: Recent Advances On Bacterial Cellulose For the Delivery Of A...mentioning
confidence: 99%
“…Stimuli-sensitive smart drug delivery carriers can be produced using BC hydrogels. 162 In this context, Park et al demonstrated the controlled drug release behavior of a BC-reinforced hydrogel system, in which a semi-interpenetrating network was obtained with BC nanofibers and polyacrylamide (PAM) meshes. It was reported that the composite hydrogels based on BC had a 3-fold higher compressive strength than the plain PAM hydrogels.…”
Section: Recent Advances On Bacterial Cellulose For the Delivery Of A...mentioning
confidence: 99%
“…The SMPs include hydrogels that can change their volume in response to stimuli [ 15 ]. These are hydrophilic in nature, showing swelling and de-swelling behaviour.…”
Section: Raw Materialsmentioning
confidence: 99%
“…[ 1,2,3 ] However, their intrinsic poor water solubility and low bioavailability have limited their translation to clinical development. [ 4,5,6,7,8 ] Despite extensive hydrogel‐based materials have been successfully developed and achieved some improvements in such unfavorable properties, [ 9,10,11 ] some challenges, like low bioactivity and burst release of flavonoid, remain. Overcoming the detrimental effects has proven to be exceptionally difficult because flavonoids are more effective to relieve complicated diseases in a multi‐targets/multi‐components manner.…”
Section: Introductionmentioning
confidence: 99%